2019
DOI: 10.1002/mrm.28107
|View full text |Cite
|
Sign up to set email alerts
|

Presurgical resting‐state functional MRI language mapping with seed selection guided by regional homogeneity

Abstract: Purpose Resting‐state functional MRI (rs‐FMRI) has shown potential for presurgical mapping of eloquent cortex when a patient’s performance on task‐based FMRI is compromised. The seed‐based analysis is a practical approach for detecting rs‐FMRI functional networks; however, seed localization remains challenging for presurgical language mapping. Therefore, we proposed a data‐driven approach to guide seed localization for presurgical rs‐FMRI language mapping. Methods Twenty‐six patients with brain tumors located … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…In a recently published research study performed at our institution, we compared SBC rs-fMRI maps generated using tb-fMRI activations (apart from tumor) as seed points, an automated ReHo method, and a canonical (anatomical landmark) approach. The ReHo method yielded rs-fMRI language mapping results that were in greater agreement with the results of tb-fMRI, with significant higher Dice coefficients (p < 0.5) than that of tb-fMRI and canonical approaches within the putative language areas [19]. Based on the results of this study, we plan to formally integrate an automated ReHo method to guide SBC rs-fMRI seed placement into our clinical workflow in the near future.…”
Section: Discussionmentioning
confidence: 59%
“…In a recently published research study performed at our institution, we compared SBC rs-fMRI maps generated using tb-fMRI activations (apart from tumor) as seed points, an automated ReHo method, and a canonical (anatomical landmark) approach. The ReHo method yielded rs-fMRI language mapping results that were in greater agreement with the results of tb-fMRI, with significant higher Dice coefficients (p < 0.5) than that of tb-fMRI and canonical approaches within the putative language areas [19]. Based on the results of this study, we plan to formally integrate an automated ReHo method to guide SBC rs-fMRI seed placement into our clinical workflow in the near future.…”
Section: Discussionmentioning
confidence: 59%
“…Rs-fMRI is being increasingly used in the setting of presurgical brain mapping. 3,14,15 Despite the potential subject level variability of data accuracy, 6,7 nevertheless in select cases, rs-fMRI may be considered a viable option for presurgical brain mapping; indeed, at least 1 institution has included rs-fMRI in their presurgical brain mapping paradigm without obtaining task-fMRI. 3,16 For this purpose, obtaining highly accurate intrinsic brain network data is paramount to avoid adverse outcomes following surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Four language templates that had previously shown success for applications in presurgical language mapping were selected for this study: (1) anatomically determined with Harvard–Oxford Atlas (Caviness et al., 1996 ) (Template A), (2) generated based on tb‐fMRI study (Branco et al., 2016 ; Fedorenko et al., 2010 ) (Template B), (3) generated based on rs‐fMRI study (Shirer et al., 2012 ; Zacà et al., 2018 ) (Template C), and (4) obtained from meta‐analysis results from Neurosynth with anatomical constraints (Hsu et al., 2020 ; Yarkoni et al., 2011 ) (Template D) (Figure 1 ). More details about the construction of these atlas can be found in Section 4 .…”
Section: Methodsmentioning
confidence: 99%
“…Language brain templates typically include anterior and posterior primary language areas (PLAs), and some include other language‐associated areas that are representative of a population of subjects (Fedorenko et al., 2010 ). After spatially transformed to an individual subject's space, such templates can help clinical fMRI analysis to evaluate language laterality from tb‐ or rs‐fMRI (Agarwal et al., 2018 ; Gohel et al., 2019 ; Pillai & Zaca, 2011 ; Ruff et al., 2008 ) and to guide seed selection for mapping the language network with rs‐fMRI (Hsu et al., 2020 ). In addition, previous studies have demonstrated the feasibility of categorizing functional networks from independent component analysis (ICA) of rs‐fMRI by using an automated template‐matching process and showed success in identifying language networks for presurgical mapping (Branco et al., 2016 ; Tie et al., 2014 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation